Desain Sistem Pengadaan Barang Inventaris dengan Pendekatan SDLC dan Waterfall - Nazwa Alya Faradita; Warda Hamidah; Armansyah Armansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Procurement of goods, tools, and production materials within a company is a crucial process in maintaining smooth operations and efficiency. However, there are often challenges in managing the procurement process, such as lack of transparency, administrative complexity, and lack of integration between the procurement system and the inventory system. This research aims to develop a procurement application for goods, tools, and production materials using the System Development Life Cycle (SDLC) and Waterfall approach to ensure a structured development process. The research method involved observations and interviews to understand user needs as well as analysis of the existing system. The results of this research summarize the design of an application that improves the procurement process, increases transparency, and strengthens the integration between procurement and inventory management. This application is expected to contribute to improving the efficiency of procurement management in a corporate environment.